2022
DOI: 10.3390/catal12030256
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Gas Production from Two-Stage Catalytic Pyrolysis of Pine Sawdust with Nano-NiO/Al2O3 Catalyst

Abstract: Hydrogen production from biomass pyrolysis is economically and technologically attractive from the perspectives of energy and the environment. The two-stage catalytic pyrolysis of pine sawdust for hydrogen-rich gas production is investigated using nano-NiO/Al2O3 as the catalyst at high temperatures. The influences of residence time (0–30 s) and catalytic temperature (500–800 °C) on pyrolysis performance are examined in the distribution of pyrolysis products, gas composition, and gas properties. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Morgan et al [82] observed that longer residence times produced less bio-oil and char and higher syngas and volatile yields. Xu et al [83] studied hydrogen-rich gas production from two-stage catalytic pyrolysis of pine sawdust with Nano-NiO/Al 2 O 3 catalyst. Their results showed that, at longer residence times, the bio-oil and char yields decreased whereas gas yield increased.…”
Section: Residence Timementioning
confidence: 99%
“…Morgan et al [82] observed that longer residence times produced less bio-oil and char and higher syngas and volatile yields. Xu et al [83] studied hydrogen-rich gas production from two-stage catalytic pyrolysis of pine sawdust with Nano-NiO/Al 2 O 3 catalyst. Their results showed that, at longer residence times, the bio-oil and char yields decreased whereas gas yield increased.…”
Section: Residence Timementioning
confidence: 99%
“…The NiO-Al 2 O 3 nanocomposites thus synthesized have been used for applications such as partial oxidation of methane to syngas, [16] removal of congo red, [17] photocatalysis, [18] oxidation of styrene, [9] and hydrogen rich gas production. [19] Metal oxide nanocomposites have a general tendency to agglomerate due to their high surface energy and high surface to volume ratio. They often do not have suitable surface properties for specific applications, e. g. oil recovery, [20] removal of toxic ions, [21] antibacterial agents, [22] drug delivery, [23] and removal of toxic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…There are many methods reported for the synthesis of NiO‐Al 2 O 3 nanocomposites, e. g. hydrothermal method, [14,17] sol‐gel method, [15] sol‐gel followed by electrospinning, [18] etc. The NiO‐Al 2 O 3 nanocomposites thus synthesized have been used for applications such as partial oxidation of methane to syngas, [16] removal of congo red, [17] photocatalysis, [18] oxidation of styrene, [9] and hydrogen rich gas production [19] . Metal oxide nanocomposites have a general tendency to agglomerate due to their high surface energy and high surface to volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Thermochemical conversions stand out for their cost-effectiveness and the relative maturity of the technology. They excel in decomposing carbonaceous materials, breaking chemical bonds, and harnessing energy efficiently [9,10]. Pyrolysis involves transforming biomass into char, bio-oil, and gases-predominantly carbon monoxide (CO), hydrogen (H 2 ), carbon dioxide (CO 2 ), and methane (CH 4 )-within a high-temperature, oxygen-free environment.…”
Section: Introductionmentioning
confidence: 99%